The Influence of Transformational Leadership Style and Military Organizational Culture on Soldier Performance at Makorem 101/Antasari - Ari Aryanto; Ahmad Alim Bachri; Anisah, Hastin Umi (HM Publisher, 2024)
Improving the quality of soldier performance is greatly influenced by leadership and organizational culture. The aim of this study is analysis the influence of transformational leadership style and military organizational culture on the performance of soldiers in Makorem 101/Antasari. The research method is quantitative using partial least squarewith data analysis using Smart PLS 3.0 software. The study population consists of 100 soldiers from the Military Regional Command (MAKOREM) 101/Antasari. The result shows that transformational leadership style and military organizational culture on soldier performance.